Arabinoxylan from Mucilage of Tomatoes (Solanum lycopersicum L.): Structure and Antinociceptive Effect in Mouse Models - do Nascimento, Georgia Erdmann; Baggio, Cristiane H; Werner, Maria Fernanda de Paula; Iacomini, Marcello; Cordeiro, Lucimara M C (Journal of agricultural and food chemistry, 2016)
Tomato is a known functional food due to its content of bioactive compounds. Herein, polysaccharides were extracted from mucilage of tomatoes, and a purified fraction (PTOK) was analyzed by sugar composition, methylation, and NMR spectroscopy analysis. The results showed the presence of an arabinoxylan, having (1→4)-linked β-d-Xylp units in the main chain, which carried a low proportion of branching (∼5.6%), at O-2 and O-3 position, with side chains constituted by single Araf or Xylp units. Intraperitoneal administration of the arabinoxylan in mice significantly reduced the number of abdominal constrictions induced by 0.6% acetic acid and the inflammatory phase of nociception induced by 2.5% formalin, indicating that it had an antinociceptive effect on inflammatory pain models, amplifying the biological role displayed by arabinoxylans in the diet. Furthermore, this study reports the presence of an arabinoxylan in a dicotyledon plant, and also it is the first study of polysaccharides from mucilage of tomatoes.